THE INFLUENCE OF FINANCIAL LITERACY, INDIVIDUAL CHARACTERISTICS, OVERCONFIDENCE AND RISK TOLERANCE ON SHARE INVESTMENT DECISIONS (Study on Master of Management Student Faculty of Economics and Business Universitas Airlangga 2022) - Mario Zagarino Laning; Rahmat Setiawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the influence of financial literacy, individual characteristics, overconfidence and risk tolerance on stock investment decisions. This research uses quantitative methods. The measurement method in this study was to use an online interview questionnaire instrument via G-Form. The source of data in this study is from the report on the value of capital market investment and inflation from the IDX website (Indonesia Stock Exchange) during the 2019-2021 period. The total population was master of management students who are actively investing which consist of 373 students. The overall population was used as the sampling approach in this investigation. The findings revealed that the financial literacy variable has a value of 0,000, where the value < 0,05. The age variable has a value of 0,631, where the value > 0,05 which means that there is no influence of the age variable on investment decisions. The gender variable has a test result value of 0,996, where the value > 0,05, which means that there is no significant influence between gender and investment decisions. The overconfidence variable has a test result value of 0,002, where the value < 0,05, which means that there is a significant influence between overconfidence and investment decisions. The risk tolerance variable has a test result value of 0,03, where the value < 0,05, which means that there is a significant influence between risk tolerance and investment decisions.